Cover Image. (22nd October 2021) - Nolan, Rachael H.; Collins, Luke; Leigh, Andy; Ooi, Mark K.J.; Curran, Timothy J.; Fairman, Thomas A.; Resco de Dios, Víctor; Bradstock, Ross
Abstract : The cover image is based on the Invited Review Limits to post‐fire vegetation recovery under climate change by Rachael H. Nolan et al., https://doi.org/10.1111/pce.14176 . Abstract : The cover image is based on the Invited Review Limits to post‐fire vegetation recovery under climate change by Rachael H. Nolan et al., https://doi.org/10.1111/pce.14176 .